Research on the innovation of time-honored brands from the perspective of dual ethical patterns - Ke, Di; Li, Guodong; Jiang, Yichen; Li, Yuanyuan; Liu, Yi (Frontiers in Psychology, 2023)
Introduction Innovation has become an important means to promote the high-quality development of time-honored brands. However, the research on how to stimulate innovation investment in time-honored brands, especially that conducted in the local context, is still rare. To supplement the research limitations, this study adopts the perspective of dual ethical patterns and is set in the domestic context to explore the ethical influence of traditional cultures and marketization on the innovation investment of time-honored brands. Methods We proposed two complementary methods, which are OLS regression and fsQCA analysis respectively, to systematically analyze the mechanism and key path of the dual ethical pattern to promote the innovation of time-honored brands. Results The results show that traditional culture and marketization level are both positively related to the innovation of time-honored brands. However, traditional culture and marketization level are mutually exclusive in their process of affecting the innovation of time-honored brands. Discussion This paper advances time-honored brands literature by highlighting the dual ethic pattern formed by traditional culture and marketization level on the innovation investment of time-honored brands. The findings respond to the academic debate between traditional culture and the innovation of time-honored brands, while enriching the research scope on the innovation mechanism of time-honored brands in the local context.